Keabsahan Perkawinan Kedua Penganut Katolik Tanpa Adanya Anulasi Setelah Perceraian Perkawinan Pertama (RechtJiva, 2025)
Marriage in the Catholic Church is sacramental, unity, and indissolubility so that there is no concept of divorce to break a Catholic marriage bond. However, in the practice of national law, divorce is recognized as one of the legal ways to break a marriage as stipulated in Law No. 1 of 1974 concerning Marriage. This study aims to analyze and examine the legal status of second marriages conducted by Catholics, whose first marriages have been divorced by the court but have not been annulled through the annulment process by the Catholic Church Court. The approach used in this research is normative juridical by examining relevant laws and regulations, canon law, and court decisions as case examples. The results of this study indicate that the concept of marriage in Canon Law and the Marriage Law both adhere to the principle of monogamy, but differ in their application. The Marriage Law allows polygamy under certain conditions, while Canon Law is absolute. The concept of annulment of marriage in Canon Law is different from the concept of annulment of marriage and divorce in the Marriage Law, from the conditions that must be met, the process, to the legal consequences. In addition, this study also found that a second marriage for Catholics without annulment from the Church for their first marriage will result in the invalidity of the second marriage because divorce from the court does not erase the first marriage bond that is valid according to Canon Law and the Catholic Church.